Petroleum alteration by thermochemical sulfate reduction – A comprehensive molecular study of aromatic hydrocarbons and polar compounds. (15th March 2015) - Walters, Clifford C.; Wang, Frank C.; Qian, Kuangnan; Wu, Chunping; Mennito, Anthony S.; Wei, Zhibin
Abstract: Thermochemical sulfate reduction (TSR) alters petroleum composition as it proceeds towards the complete oxidation of hydrocarbons to CO2 . The effects of TSR on the molecular and isotopic composition of volatile species are well known; however, the non-volatile higher molecular weight aromatic and polar species have not been well documented. To address this deficiency, a suite of onshore Gulf coast oils and condensates generated from and accumulating in Smackover carbonates was assembled to include samples that experienced varying levels of TSR alteration and in reservoir thermal cracking. The entire molecular composition of aromatic hydrocarbons and NSO species were characterized and semi-quantified using comprehensive GC × GC (FID and CSD) and APPI–FTICR-MS. The concentration of thiadiamondoids is a reliable indicator of the extent of TSR alteration. Once generated by TSR, thiadiamondoids remain thermally stable in all but the most extreme reservoir temperatures (>180 °C). Hydrocarbon concentrations and distributions are influenced by thermal cracking and TSR. With increasing TSR alteration, oils become enriched in monoaromatic hydrocarbons and the distribution of high molecular weight aromatic hydrocarbons shifts towards more condensed species with a decrease in the number of alkyl carbons. Organosulfur compounds are created by the TSR process. In addition to the increase in benzothiophenes and dibenzothiophenes noted in previous studies, TSR generates condensed species containing one or more sulfur atoms that likely are composed of a single or multiple thiophenic cores. We hypothesize that these species are generated from the partial oxidation of PAHs and dealkylation reactions, followed by sulfur incorporation and condensation reactions. The organosulfur species remaining in the TSR altered oils are "proto-solid bitumen" moieties that upon further condensation, oxidation or sulfur incorporation result in highly sulfur enriched solid bitumen, which is chemically distinct from pyrobitumen formed by thermal cracking reactions. Although TSR involves the oxidation of hydrocarbons to CO2, prior studies of TSR-altered oils have not identified intermediate products. Using NESI–FTIRC-MS, the presence and distribution of oxygenated species become evident. All oils possess minor amounts of O2 and O4 species, presumable mono- and di-naphthenic acids originating from the source. As TSR progresses, the distribution of oxygenated species shifts towards increasing species with higher oxygen content, up to O8 . Similar trends are observed for the SO x species. We hypothesize that these are partially oxidized condensed hydrocarbons and that these species are likely formed by the reaction proposed by Püttmann et al. (1989) for the oxidation of PAHs associated with Kupferschiefer mineralization, whereby hydrocarbons with aryl–aryl bonds incorporate sulfur to form thiophenic species. The rate of TSR is influenced by reservoir temperature and the presence of H2 S. Typically, high reservoir temperatures (>140 °C) are needed for extensive TSR alteration to occur. Oil from the Gin Creek Field appears to have received a charge of H2 S, presumably from TSR alteration of a down dip reservoir, which has accelerated the TSR reaction within a relatively cold reservoir (∼109 °C). This condition has allowed for the generation and preservation of abundant sulfur containing species that would be thermally cracked at higher temperatures.